Species Distribution Pattern and Their Contribution in Plant Community Assembly in Response to Ecological Gradients of the Ecotonal Zone in the Himalayan Region - Inayat Ur Rahman (MDPI AG, 2021)
The ecotonal zones support populations that are acclimated to changing, fluctuating, and unstable conditions, and as a result, these populations are better equipped to adjust to expected change. In this context, a hypothesis was tested that there must be vegetation dominated by unique indicator plant species under the influence of ecological gradients in the ecotonal zone of Manoor Valley (northwestern Himalaya), Pakistan. Keeping the aforementioned hypothesis in mind, detailed field studies were conducted during different seasons in 2015-18. Line transect sampling and phytosociological characteristics (density, frequency, cover, and their relative values and Importance Value) were implemented as ecological methods. This investigation documented 97 plant species recorded from seven sampling sites. The community distribution modelling revealed that the ecological variables separate the seven sampling sites into two major plant communities (Indigofera-Parrotiopsis-Bistorta and Ziziphus-Leptopus-Quercus) recognized by TWINSPAN. The IBP communities showed a positive and significant correlation with altitude (1789.6–1896.3 m), sandy soil texture with a slightly acidic pH (6.4–6.5), and higher phosphorous (9–13 mg kg−1). In contrast with this, the ZLQ community was recognized on the southern slope under the strong influence of high electrical conductivity (2.82–5.4 dsm−1), organic matter (1.08–1.25%), calcium carbonate (5.8–7.6 mg kg−1), potassium (202–220 mg kg−1), and temperature (28.8–31.8 °C). Hence, both communities were found on opposite axes with clear differences based on the ecological gradients. NMDS clustered different species with similar habitats and different stands with common species, showing that plant species and stands were in a linear combination with ecological gradients. The IPB community has the maximum number of plant species (87 species), Shannon value (H’ = 4), Simpson value (0.98), and Pielou’s evenness value (0.96). Thus, the multivariate approaches revealed unique vegetation with sharp boundaries between communities which might be due to abrupt environmental changes.